Stravinsky’s cut-and-paste compositional technique with commentary on whither no one knows, an original work - Worcester, Benjamin (Kansas State University, 2010)
Igor Stravinsky used a compositional technique that researchers have termed cut-and-paste. During the compositional process, Stravinsky would write notes on carbon paper, then cut the lower parts out to paste them into other sheets of paper with music on them. This paper examines a few key ways this fits into the compositional process for Symphonies of Wind Instruments (1920, rev. 1947). In an original work, Whither No One Knows (a chamber work for flute, clarinet, marimba, piano, violin, viola, and cello) several similar cut-and-paste compositional processes were used. These include melodic cut-and-paste, ostinato creation, layering, rhythmic diminution, and extension. These techniques are illustrated and examined. The full score of Whither No One Knows (2009) is included.
Keywords: Music; Composition technique; Igor Stravinsky; Music (0413)